(untitled) (Modern education and development, 2024)
The study of renal anatomy is fundamental to understanding kidney function and the management of various renal diseases. This research emphasizes the crucial role of nursing practice in renal anatomy education. Nurses are not only instrumental in clinical practice but also in educating patients, assisting in procedures, and contributing to medical research. The purpose of this article is to highlight the significance of nursing involvement in the study and understanding of renal anatomy, exploring how nurses support the clinical and educational aspects of kidney health.